Integrasi Pendidikan Agama Hindu Dengan Kearifan Lokal Dalam Pembelajaran - K. Eka Dwipayanti (Prodi PGSD Unsultra, 2023)
Hindu religious education plays a crucial role in shaping students' character and morals. One approach to enhancing learning is integrating religious values with local wisdom prevalent in society. This literature study aims to examine the concept of integrating Hindu religious education with local wisdom in learning and its implications for students' character development. The study employs a literature analysis method, drawing from various academic sources, books, and relevant journals. The findings indicate that integrating Hindu religious education with local wisdom enhances students' understanding of religious teachings within a cultural context closely related to their daily lives. Local wisdom values such as tat twam asi (awareness of unity), tri hita karana (harmony in life), and the wisdom embedded in religious ceremonies serve as effective mediums in religious education. Furthermore, this approach strengthens cultural identity and increases students' social awareness. Therefore, the implementation of this integration in learning requires greater attention from educators and educational policymakers.